Psichologiceskij podchod k formirovaniju gruppovoj splocennosti komandy basketbolistov s ucetom ich individual'nych charakteristi - Lozovoy, A. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
This paper presents a study of changes in the state of group cohesion high school basketball team of high school education as a result of application of the developed technique. The developed technique was selected taking into account the psychological characteristics of the players. For the group cohesion school basketball team formation we selected following tools and methods: autogenous training, the use of logic methods, self-commands and images, goal-oriented situation visualization, distraction techniques, deliberate muscle tone management, voice state, breathing as self-regulation, the use of exercise to control the mental state. Applying the developed method showed that the total score by Seashore method in both teams reached high rating. But in the experimental team the difference in points was 2.8 points, compared with the control which was 0.9 points. Average rates increase in the experimental group was: evaluation of personal information - by 29.7%, evaluation of communicative information - by 16.1%, evaluation of group information - by 18.8%, the index of group cohesion - 13.1%. The cohesion coefficient increased by 18.6%. In the control group, the average increase was: evaluation of personal information - by 12.3%; evaluation of group information - by 7.7%; evaluation of communicative information - by 7.7%; cohesion coefficient - by 2.4%.